A structural and vibrational study of dehydrofukinone combining FTIR, FTRaman, UV–visible and NMR spectroscopies with DFT calculations - Lizarraga, Emilio Fernando (2013)
The vibrational and electronic properties of 4b,5b-eremophil-7(11)9-dien-8-one, also known as dehydrofukinone (DHF), have been investigated by using experimental FT-IR, FT-Raman, NMR and UV spectra techniques and density functional theory (DFT) employing B3LYP exchange correlation with the 6-31G and 6-311++G basis sets. The calculated vibrational frequencies and the chemical shifts were successfully compared with the corresponding experimental values. The DFT calculations were combined with the Pulay’s scaled quantum mechanical force field (SQMFF) methodology in order to perform a complete assignment of the observed bands in the vibrational spectra. The comparison of the theoretical ultraviolet–visible spectrum with the corresponding experimental demonstrates a good concordance. The natural bond orbital (NBO) study reveals for the isopropyliden and the two rings of DHF the characteristics of the electronic delocalization, while the corresponding topological properties of electronic charge density were analyzed by employing Bader’s Atoms in the Molecules theory (AIM).